Aleksandr Yevgenievich Loskutov - "ORTHOPAEDICS, TRAUMATOLOGY AND PROSTHETICS", Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
May 26, 2020 marks the 70th anniversary of the birth and 47 years of medical, scientific, pedagogical and social activities of the Academician of the National Academy of Medical Sciences of Ukraine, Honored Worker of Science and Technology of Ukraine, laureate of the State Prize of Ukraine, Head of the Department of Traumatology and Orthopedics of the Dnipropetrovsk Medical Academy, Doctor of medical sciences, professor Loskutov Aleksandr Yevgenievich.